In vitro digestibility and fermentability of fructo-oligosaccharides produced by Aspergillus ibericus. (July 2018) - Nobre, C.; Sousa, S.C.; Silva, S.P.; Pinheiro, A.C.; Coelho, E.; Vicente, A.A.; Gomes, A.M.P.; Coimbra, M.A.; Teixeira, J.A.; Rodrigues, L.R.
Graphical abstract: Highlights: FOS produced by Aspergillus ibericus showed great potential as prebiotics. Microbial-derived FOS promoted higher cellular growth of the probiotic strains. FOS from A. ibericus (>98.5%) resisted the in vitro digestive system conditions. A. ibericus and A. pullulans produce neoFOS, possibly blastose and neokestose. Abstract: The bifidogenic potential of fructo-oligosaccharides (FOS) produced by a newly isolated strain – Aspergillus ibericus was studied. Their activity was compared to FOS produced by Aureobasidium pullulans and to a non-microbial commercial FOS sample (Raftilose ® P95). FOS fermentability by a number of probiotic bacteria and their hydrolytic resistance to the simulated harsh conditions of the digestive system was evaluated. Aspergillus ibericus FOS sample effectively promoted probiotic bacteria growth. Overall, microbial-derived FOS promoted greater cellular growth compared to the commercial sample. FOS fermentation was both substrate and strain specific. The FOS structural differences identified may explain their distinct assimilation by the probiotics. [Fru(2→6)Glc] (possibly blastose) and a reducing trisaccharide (possibly [Fru(β2→6)Glc(α1↔β2)Fru], neokestose) were only found in microbial-derived FOS samples, while Raftilose ® P95 was richer in inulobiose/inulotriose. 1-Kestose and nystose were only slightly hydrolyzed in the presence of gastric and intestinal fluid. FOS synthesized by Aspergillus exhibited great potential as food ingredients with likely prebiotic features.